Isolation and identification of cellulose degrading bacteria from soil sample - Abedin, Jerin Isnat (BRAC University, 2015)
A Dissertation Submitted in Partial Fulfillment of the Requirements’ for the Degree of B.Sc. in Microbiology 2015.